A field guide to actor training : navigating acting methods, studio classes, private training, and graduate and undergraduate programs - Wayth, Laura (Milwaukee, WI : Applause Theatre & Cinema Books, 2014)
""Should I go to a school and get more training in acting, or should I just go out there and 'do it'?" A Field Guide to Actor Training will help you answer this question! The book is designed to be an introduction to various theater training methodologies, highlighting their basic tenets and comparing and contrasting each system of training and rehearsal. The goal is to provide a one-stop-shopping kind of resource for student/beginning actors who are seeking training through private studios or graduate schools and who crave guidance in selecting training that is right for them. [Wayth starts] with the big question of "Why is actor training important?" and mov[es] on to overviews of the major acting methodologies, vocal training, physical actor training, and advice on how to find the right kind of training for each individual ..."--Publisher's description.
The big questions -- Why actor training is important -- Stanislavsky, the foundation of it all -- Lee Strasberg and The method / by Professor Terry Hardcastle -- -- Practical aesthetics technique -- Michael Chekhov technique -- Meisner technique -- Stella Adler -- Uta Hagen -- Viewpoints -- Suzuki method -- Spolin and improv -- Grotowski -- Demystifying vocal training -- Demystifying physical acting training -- A look at degree-granting training programs -- A student Q & A session.
Includes bibliographical references (pages 233-237) and index.
Keywords: Acting -- Study and teaching; Acting -- Study and teaching